EVALUATION OF HVOF SPRAYED WC-13Co-4Cr AND HARD CHROMIUM ELECTROPLATED ON STAINLESS STEEL 15-5PH FATIGUE STRENGTH - Silva Junior, Gilson [UNESP]; Voorwald, Herman J. C. [UNESP]; Odila, Maria [UNESP]; Cioffi, Hilrio [UNESP]; Gomes, JFS; Meguid, S. A. (Inegi-feup, 2017)
Fatigue failure is the result of a crack initiation and propagation as a consequence of cyclic loading. In the aeronautical industry, for components like landing gear, fatigue strength is an important parameter to be considered in project, as well as the corrosion and wear resistance. The 15-5 PH stainless steel is an aeronautical material used in applications that require high mechanical strength and corrosion resistance. Nevertheless its application is restricted due to low wear resistance. Therefore a hardening surface treatment is necessary. Nowadays the most applied surface hardening process in the aircraft industry is Chromium Electroplated, which increases the corrosion and wear resistance. Even considering satisfactory results, the use of hard chromium process has been restricted due to environment impact and to the human health. The main objective of this research was to study the influence of WC-13Co-4Cr HVOF thermal spray coated in the axial fatigue strength of 15-5PH stainless steel. Experimental results were compared with chromium electroplated. Compressive residual stress induced by the shot peening process were responsible for the increase in the fatigue life of HVOF coated material.
Keywords: Thermal spray coatings; fatigue; 15-5PH steel; shot peening